Heterogeneidade temporal-vertical de recursos florais e seus efeitos em comunidade de abelhas - Chamorro García, Fermín José (2021)
Flowering phenodynamics and stratification are vegetation attributes that are rarely studied in combination, but together they contribute to the maintenance of species diversity by helping to understand the effects of temporal-vertical heterogeneity of resources on species coexistence. Floral resources are the main regulating factor of bee populations and diversity, but their understanding from the perspective of temporal-vertical heterogeneity and the responses of bees to this variation are still limited. This knowledge will assist in bee conservation actions through guiding vegetation management practices that favor phenological complementarity within and between habitats, thus maintaining the taxonomic and functional diversity of bees. For this purpose, during a period of 18 months, I monthly collected data on f the flowering phenodynamics of the herbaceous and shrub/tree strata in the plant community and on the diversity of bees in each stratum in three 0.5 ha plots established in three fragments of Caatinga, semi-arid region of Brazil. The analysis of the plant community in these plots was carried out by life forms and growth forms and their phenodynamics was related to water availability and photoperiod. For bee sampling, I used three methods: pan traps distributed at different heights (0.3m, 1.6m, 4.0m), large blue bucket and entomological net. From these samples, I characterized the bee community and its temporal variation. Also, I analyzed the importance of the vertical dimension in the optimization of bee sampling with pan traps, the main recommended method for monitoring populations and diversity of bees. To understand the effects of temporalvertical availability of floral resources on the performance of bee sampling methods and on species coexistence, I analyzed different community attributes: abundance, richness, taxonomic diversity, functional diversity, taxonomic and functional beta diversity. About 80% of the plant species recorded in both strata of vegetation constitute an important source of floral resources for bees. During the study, bees experienced different periods of floral resources availability, which derived from the different responses of life forms and growth forms to environmental conditions. The plant community presents intra and interspecific temporal differences in flowering phenodynamics, providing a continuous supply of resources throughout the year, including in the dry season, when almost all species lose their leaves. However, there are months in which resources are available only in the woody layer, only in the herbaceous layer, in both strata during the rainy season, in both strata during the dryperiod, and without resources in both strata in the dry period. The increase in the floral resources availability with the simultaneous flowering of woody and herbaceous layer affected the performance of the pan traps by decreasing the abundance and richness captured with this method. However, the elevated pan traps captured species not detected by the lower pan traps or by other methods. Therefore, with the elevation of the pan traps, it was possible to capture bees that forage at a specific height, which allowed a better characterization of the bee community and to obtain evidence of the influence of the temporal-vertical heterogeneity of floral resources in the coexistence of bees. I demonstrated that the different periods of floral resources availability matter for the maintenance of the diversity of bees in the Caatinga. This heterogeneity creates temporal niches that favors bees foraging at specific heights, especially at the beginning of the dry season when floral resources are still stratified, allowing the increase of species diversity. In this period, there are still abundant resources in the herbaceous layer, mass flowering of woody plants and climatic conditions that facilitate the foraging of a greater number of bee species. In short, this thesis demonstrated that understanding the vertical dimension of floral resources availability for bees is crucial to optimize the sampling and conservation of such important pollinators in environments with stratified vegetation. The thesis was structured in five sections: 1) Introduction / theoretical review of the thesis’ theme, presenting the justification for the importance of vertical-temporal heterogeneity of floral resources, particularly in relation to the characterization of bee communities and the understanding of coexistence mechanisms of bees in semiarid environments, 2) Description of the flowering phenodynamics of the plant community by life forms and growth forms and their phenological complementarity to provide floral resources for bees, 3) Analysis of bee sampling performance when using pan traps vertically distributed in the vegetation and the influence of the temporal-vertical availability of floral resources on this performance, 4) Using data from sections 2 and 3, I investigate the central question of the thesis: what is the influence of temporal-vertical availability of the floral resources on the coexistence and organization of the bee community? and 5) Synthesis and general conclusion of the thesis and its potential to effectively strengthen bee conservation actions.